The impact of dietary diversity and seasonality in food availability on the quantile distribution of birth size among pregnant women in rural Malawi - a cross-sectional study - Katrine G. Hjertholm; Gerd Holmboe-Ottesen; Ibrahimu Mdala; Zumin Shi; Per O. Iversen (BMC, 2022)
Abstract Background Dietary diversity scores can be used as a proxy for dietary intakes and for assessment of nutrient adequacy. Studies from low-resource settings have found maternal dietary diversity scores to be associated with neonatal birth size. We here investigated the relationship between the dietary diversity score among pregnant mothers and birth size of their offspring across quantiles of the birth size variables; birth weight, length, abdominal circumference, and head circumference. We also investigated if seasonality affects birth size across different quantiles. Methods Dietary intake and anthropometric data were collected from 190 pregnant women and their neonates in rural Malawi through two agricultural seasons. Dietary data was collected using 24-hour recall interviews and was categorized into the 10-food group dietary diversity score proposed for women by the Food and Agriculture Organization. Neonatal anthropometrics were collected upon delivery at health facilities. Quantile regression analyses were used to investigate associations between dietary diversity scores and birth size, as well as between seasonality and birth size. Results We found that neonatal abdominal circumference was 0.9 cm larger during the post-harvest season compared to the pre-harvest season among neonates in the 25th quantile. Birth weight was 281.4 g higher for those born during the post-harvest season in the 90th quantile. For a one-unit increase in maternal dietary diversity score, birth weight increased by 56.7 g among those in the 25th quantile and neonatal head circumference increased by 0.2 cm for those in the 70th quantile. However, these findings did not remain significant when considering the cluster effect of the neonatal anthropometric data. Conclusions Our findings indicate that the relationship between seasonality and birth size differs across the distribution of birth size. Investigating the effect of seasonality across the distribution of birth size could be important to identify vulnerable subgroups and develop better, targeted interventions to improve maternal and child nutrition and health.